Pengaruh Budaya Religius Madrasah Terhadap Sikap Moderasi Beragama Siswa Di MAN 3 Jombang - Ashoumi, Hilyah; Rahmawati, Dewi Saroh (Universitas KH. A. Wahab Hasbullah, 2023)
This research is based on the phenomenon of the concept of religious moderation in madrasas. In connection with this, this study aims to determine the effect of madrasah religious culture on religious moderation attitudes at MAN 3 Jombang. This research is a quantitative research. The population and samples in this study were X and XI grade students at MAN 3 Jombang, totaling 100 people. Data collection using a questionnaire, and data analysis using simple regression analysis techniques. This study concluded that Madrasah Religious Culture has a significant influence on the attitude of religious moderation at MAN 3 Jombang, as evidenced by the Sig value = 0.01 < α = 0.05. The correlation coefficient value (r) = 0.951 or contributes 95.1%